Comparison of Transportation Service Tariffs Between Maxim and Gojek Transportation Services (Study on Students, Faculty of Economics and Business, Victory University, Sorong) - Panggarra, Rasdy; Susana Magdalena Welly Mustika (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This study contains a comparison of transportation service rates between maxim and gojek transportation services, an example of a Case Study of Students of the Faculty of Economics and Business, Victory University, Sorong. Using the Sample T-Test test method. With the results of this research analysis showing the average or mean for the maxim price is 16,886 with a standard deviation of 2.6280 and a standard error mean of 0.2801, meanwhile, the average gojek price is 14,659. 886 with a standard deviation of 3.5554 and a standard error mean of 0.3790. Descriptively statistically there is a difference in the average price between the maxim price and the gojek price. The second output result obtained the Sig. leven's test for equality of variances 0.111> 0.05 data variance between the maxim price and the gojek price is the same. The independent sample t-test test presented the results of H0, rejected and Ha accepted. The mean data difference shows data of 2.2273. This value shows the difference between the results of the average value of Maxim prices and the average value of Gojek prices or 16,886-14,659 = 2,227, the difference is 1.2971 to 3.1581 (95% Confidence interval. Comparison of T count and T table in the independent sample t-test, The T count value is 4.726 which is greater than T Table 1.974 based on the basis of decision making through a comparison of the t count value with T Table, it can be concluded that H0 is rejected and Ha is accepted. It is concluded that there is a significant comparison of Maxi and Gojek rates